Haploinsufficiency caused by a nonsense mutation in NCSTN underlying hidradenitis suppurativa in a Chinese family. (1st December 2015) - Yang, J.‐q.; Wu, X.‐j.; Dou, T.‐t.; Jiao, T.; Chen, X.‐b.; Min, M.; Cai, S.‐q.; Zheng, M.
Summary: Hidradenitis suppurativa (HS) is a chronic disease of follicular occlusion. It involves the axilla, groin, perianal and perineal regions, and is characterized by recurrent draining sinuses, skin abscesses and disfiguring scars. Loss‐of‐function mutations in the genes encoding γ‐secretase have been identified as a cause of HS. We collected skin samples from three patients with HS from a Chinese family carrying a NCSTN mutation (c.1258C>T (p.Q420X)) and three unrelated healthy controls (HCs). Expression level of nicastrin in skin tissue and cultured keratinocytes and fibroblasts of patients and HCs was determined by real‐time quantitative PCR and western blotting. We found that the mRNA and protein levels of nicastrin were significantly reduced in the whole skin, epidermis, dermis, and cultured keratinocytes and fibroblasts compared with HCs. Therefore, we conclude that haploinsufficiency of the NCSTN gene caused by the nonsense mutation c.1258C>T (p.Q420X) contributes to the occurrence of HS in this family.